An integrated literature review of the current discourse around universal design in the built environment – is occupation the missing link?. Issue 1 (2nd January 2021) - Watchorn, Valerie; Hitch, Danielle; Grant, Cathryn; Tucker, Richard; Aedy, Kathryn; Ang, Susan; Frawley, Patsie
Abstract: Purpose: To synthesise current literature regarding applications of universal design (UD) to built environments that promote social participation, identify areas of agreement and areas requiring further attention and development. Occupations refer to personally meaningful activities, which people need, want or must do as part of their daily life. Materials and methods: Recently published literature (January 2011–December 2017) relevant to UD and built environments, and pertaining to any discipline or professional area, were identified via a systematic search of databases in the EbscoHOST platform. The person–environment–occupation (PEO) model was chosen as a theoretical framework for the review, which included a sample of 33 peer reviewed journal articles. Results: The current discourse is driven more by description, discussion, and commentary than empirical approaches; although, a combination of quantitative, qualitative, and mixed methods approaches was employed. Much of the current discourse on UD and the built environment focuses on the person and the environment, with the occupations carried out in built environments and the interaction between these domains not referred to in much detail. Conclusions: Including occupations, social participation, multi- and trans-disciplinary collaboration, and multicultural perspectives in the ongoing discourse around UD would enable the concept to reach its full potential as a medium for social justice. Implications for Rehabilitation: The universal design (UD) process must account for the occupations that people perform in the built environment. Multi-disciplinary research and development, using multiple methods, is the most appropriate approach to investigate the application of UD to the built environment. Key areas of contention within the current discourse include meaningful inclusion of non-professional stakeholders, tensions between embracing and eliminating diversity and how professional education should be delivered.